Evaluation of Gilthead Seabream (Sparus aurata) Immune Response after LCDV-Sa DNA Vaccination - Leiva Rebollo, Rocío; Castro-López, María Dolores; Moreno García, Patricia; Borrego-García, Juan José; Labella Vera, Alejandro Manuel (MDPI, 2021)
Lymphocystis disease is the main viral pathology in gilthead seabream aquaculture. Currently, there are no treatments or vaccines to control this disease, thus our main goal was to construct a DNA vaccine that can be used in the future to stop the spread of this pathology in sea farms. The vaccine consisted of a plasmid DNA that contains a known viral gene. Once it was established that the vaccine drives the expression of the antigenic viral protein in fish, vaccination experiments were conducted to determine if the vaccinated fish become protected against the viral infection. In addition, the immune response triggered by the vaccine was also evaluated in order to understand the mechanisms underlying such protection. The obtained results showed that in vaccinated fish an activation of several genes relating to both the inflammatory process and the mucosal immunity were produced, as well as specific anti-viral antibodies. Although limited, our results deserve further investigation to assess the efficacy of the vaccine in bigger fish populations and to confirm the mode of action of the vaccine.
Keywords: Inmunología; DNA vaccine; Gilthead seabream; Gene expression; Immune response; Lymphocystivirus